Ovarian Histopathological Lesions by Superovulation Induction Drugs Intake in Female Rats: Lesi Histopatologi Ovarium oleh Asupan Obat Induksi Superovulasi pada Tikus Betina - Mazyed, Ibtihal K.; Al-badry, Fatima A. (Universitas Muhammadiyah Sidoarjo, 2025)
This study was conducted to determination the effects of fertility drugs on some sex hormones and the histological changes of the ovary. Forty-two of female rats were used, it divided into sevsn groups, each group containing 6 rats. The first group was fed with distilled water and feed as control group. The second and third groups were received Clomid (50 mg) for one month and two months respectively. The fourth and fifth groups were given Duphaston (10 mg) for one month and two months respectively. The sixth and seventh groups were treated with the Procreation V for one and two months. The results showed a singnificant increasing in levels of sex hormones (estrogen, progesterone and prolactin) in addition to histological damage such as the decline of ovarian follicles with congestion, edema, fibrosis, bleeding, increasing thickness of germinal layers and inflammation, as it was found that exposure to them for a period of two months is the most harmful. Highlights: Drugs increased estrogen, progesterone, and prolactin levels significantly. Histological damage: follicle loss, inflammation, fibrosis, bleeding. Two-month exposure caused the most severe ovarian harm. Keywords: Fertility drugs, ovary, progesterone, histological lesions